Population attributable fractions of cardiovascular diseases linked to lifestyle behaviors: the ATTICA study (2002–2022) - Damigou, Evangelia; Anastasiou, Costas; Kyrili, Konstantina; Barkas, Fotios; Liberopoulos, Evangelos; Michelis, Evangelinos; Pitsavos, Christos; Sfikakis, Petros P.; Tsioufis, Costas; Panagiotakos, Demosthenes (Frontiers in Cardiovascular Medicine, 2025)
IntroductionThe stagnant cost of cardiovascular disease (CVD) can be diminished with the effective management of well-known lifestyle factor modifications. However, when it comes to treating the individual and not the disease, research on these factors and their interactions is limited.AimThe purpose of this study was to evaluate the number of CVD cases that would be prevented in males/females and younger/older participants if specific lifestyle patterns were managed.MethodsThe sample was 1,988 (mean age: 45 ± 14 years, 49.7% male) individuals from the ATTICA cohort study (2002–2022), who were initially free-of-CVD. Trained health professionals evaluated combined fatal/non-fatal CVD outcomes, 2 major non-modifiable risk factors (i.e., sex and age) and 6 categories of modifiable risk factors [i.e., low/middle socio-economic status (SES), urban residence, at least one clinical, one psychological or one unhealthy lifestyle factor]. Population attributable fractions (PAF) and generalized impact fractions (GIFs) (percentage of exposure removal: 70%), were computed for each sole factor, as well as different combinations of these factors, representing different lifestyle patterns.ResultsA lifestyle pattern comprising of having a low/middle SES, urban residence, at least one clinical, psychological and unhealthy lifestyle factor was associated with a PAF of 82%; 8 out of 10 CVD cases would have been prevented if all these factors had been completely managed in the sample. The respective PAF and GIF was similar in males and females but differed significantly based on the age of the participants. PAF varied between 69% and 80%, when participants had all 5 factor categories, but were healthy (with no clinical factors) or of high SES, respectively.ConclusionThe increased burden of CVD could be significantly reduced with tailored programs focusing on managing lifestyle patterns, especially in individuals (males or females) older than 45 years-old.